The temolate for parallel branch algorithm - Baravykaitė, Milda (Lietuvos matematikos rinkinys, 2004)
The aim of this work is to propose parallel branch and bound algorithm template. For this purpose sequential template is introduced. Implementing additional features of this template some parallel branch and bound algorithms are comstructed and analyzed template.
Keywords: branch and bound algorithms; optimization; parallel algorithm